PENGARUH KINERJA KEUANGAN TERHADAP PROFITABILITAS PADA SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Saputri, Dini Okta; Valianti, Reva Maria; Mursalin, Mursalin (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to examine the effect of Inventory Turnover, Current Ratio, and Working Capital Turnover on Return On Assets in the Plantation Sub-Sector listed on the Indonesia Stock Exchange (IDX). Sampling was carried out using the Purposive Sampling method with the criteria of all Plantation Sub Sector companies listed on the Indonesia Stock Exchange (IDX) which published their financial reports consecutively during the 2018-2022 period and financial reports presented in rupiah currency. With this method a sample of 65 company financial data is obtained. The research data analysis technique uses the classical assumption test consisting of a normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear analysis, coefficient of determination test (R2) and hypothesis testing consisting of a partial test (t test) and simultaneous test (test F). The results of the study concluded that partially the Inventory Turnover and Current Ratio variables had a significant effect on Return On Assets, Working Capital Turnover did not have a significant effect on Return On Assets. The test results simultaneously variable Inventory Turnover, Current Ratio and Working Capital Turnover together have a significant effect on Return On Assets.